Method for reducing warping of float chemical strengthened sodium-aluminum-silicon cover plate glass and cover plate glass
By placing ultra-thin glass inclined during the chemical strengthening process and using gradient preheating and two-step salt-mixed strengthening technology, the problem of ultra-thin float glass warping is solved, improving the flatness and pass rate of the product, and reducing costs and molten salt usage.
Patent Information
- Application Number
- CN202411208057.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-24
AI Technical Summary
Ultra-thin float glass is prone to warping and deformation during chemical reinforcement, which affects the flatness and assembly tightness of the product. The existing methods are costly and have low product pass rate when applied on a large scale.
The method of placing glass inclinedly, with the tin side facing down, the angle between the glass and the horizontal plane is 40-60°, gradient preheating and two-step mixed salt strengthening, including the use of low- and high-concentration potassium nitrate molten salt, followed by dropping Salt treatment and annealing treatment to reduce warping value and molten salt usage.
It effectively reduces the warpage value of ultra-thin glass, improves the qualified rate of glass, reduces the use of molten salt, reduces production costs, and avoids edge collapse problems caused by temperature difference.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of glass manufacturing, and more specifically, to a method for reducing the warpage of a float chemically strengthened sodium aluminum silicon cover glass and the cover glass. Background Art
[0002] Smart phones, tablet computers and portable information terminals have been widely used. Lightweight and thin smart display panels have become a new trend, which has prompted the cover glass to develop in the direction of thin thickness, light weight and high strength. The reduction of glass thickness will amplify the adverse effects of defects on the strength of the glass body, resulting in a significant reduction in the mechanical properties of the cover glass. In order to enhance the scratch resistance of the touch screen surface and reduce drop damage, ion strengthening has become one of the important means to enhance the mechanical properties of ultra-thin float glass. Its mechanism of action is based on the migration and diffusion characteristics of ions on the glass surface and ions in the molten salt. The alkali metal ions with small radius in the glass are exchanged with the alkali metal ions with large radius in the molten salt, which produces a crowding effect on the glass surface, making the glass surface in a compressive stress state, thereby achieving the effect of enhancing the strength of the glass, while improving the microhardness, wear resistance, thermal stability and chemical stability of the glass, and reducing the brittleness of the glass. However, during the chemical strengthening process, the ultra-thin float glass panel is prone to warping and deformation due to uneven stress distribution on the upper and lower surfaces, which damages the flatness of the glass, and the tightness of the cover glass and the display panel components, as well as the tightness of its assembly with the display device, which affects the appearance and quality of the product and also affects the use of downstream manufacturers in the product chain. Therefore, the warping problem of ultra-thin glass panels during ion strengthening has seriously restricted the application and development of ultra-thin float glass.
[0003] Tin ion penetration into float glass is one of the reasons for warping. In addition, the larger the area of the glass sheet, the easier it is to warp during the chemical strengthening process. The chemical strengthening method currently used in the industry is standing glass placement, and the ion exchange temperature for chemical strengthening is generally between 420-460℃. Within this chemical strengthening temperature range, the particles in the glass will migrate and deform under the combined effect of gravity, i.e. warping.
[0004] Patent CN108516702B discloses a method for reducing the warping generated during chemical strengthening of glass and a strengthening jig. In this method, before chemically strengthening the glass, the glass is laid flat with the tin side of the glass facing downward. The strengthening jig is used in the above method to support the glass and lay it flat. Although this method can reduce the warping value of float glass during chemical strengthening to a certain extent, when this method is used for strengthening ultra-thin glass, a large number of ultra-thin glass sheets are placed on the jig, which will cause the glass to be easily broken during the process of entering and exiting the tempering furnace before and after tempering, and the product qualification rate is low; at the same time, this treatment method will take away more molten salt, which reduces the service life of the molten salt during the chemical strengthening process; in addition, although this patent designs a strengthening jig, if it is applied on a large scale in cover plate manufacturers, this jig will be used to replace the existing strengthening jig, which increases the cost.
[0005] The warping problem of ultra-thin float glass after ionomer strengthening is a common problem in the industry. Therefore, there is an urgent need for a simpler and more economical method to reduce the warping value of ultra-thin float cover glass after tempering. Summary of the invention
[0006] In order to solve the problem that the ultra-thin float glass is prone to warping during the chemical strengthening process and the molten salt life is easily reduced, the present application provides a method for reducing the warping of float chemically strengthened sodium aluminum silicon cover glass and the cover glass.
[0007] This application adopts the following technical solutions:
[0008] A method for reducing the warping of a float chemically strengthened sodium aluminum silicon cover glass, wherein the thickness of the cover glass is 0.4-0.7 mm, and the area of the cover glass is 420×260 mm;
[0009] The method includes:
[0010] (1) placing the cover glass to be treated in a tempering frame in an inclined manner, with the tin surface of the cover glass facing downward, and the angle between the cover glass and the horizontal plane is 40-60° when the cover glass is inclined;
[0011] (2) placing the tempered frame in a preheating furnace and performing a gradient preheating treatment at 170-440° C.;
[0012] (3) The preheated tempered frame is transferred to a tempering furnace and chemically strengthened twice in potassium nitrate molten salt with different concentrations, and then salt dripping treatment and annealing treatment are performed in sequence.
[0013] Furthermore, the above-mentioned gradient preheating treatment includes:
[0014] The tempered frame is placed in a preheating furnace at 170-210°C, and the first stage of heating is completed within 40-60 minutes, and the temperature is raised to 270-310°C;
[0015] Then, the second stage of heating is completed within 10-30 minutes, and the temperature is raised to 360-380°C;
[0016] The third stage of heating is completed within 40-60 minutes, and the temperature is raised to 410-440°C.
[0017] Furthermore, the chemical strengthening includes:
[0018] Putting the cover glass into the first molten salt and strengthening it at 380-390° C. for 8-10 hours;
[0019] The cover glass is then placed in a second molten salt and strengthened at a temperature of 410-430° C. for 1.5-2.5 hours.
[0020] Furthermore, the first molten salt is a mixed solution of potassium nitrate and sodium nitrate in a concentration ratio of (55-65):(35-45); the second molten salt is a mixed solution of potassium nitrate and sodium nitrate in a concentration ratio of (95-99):(1-5).
[0021] Furthermore, the temperature of the above-mentioned salt dripping treatment is 360-400° C. and the time is 5-20 minutes.
[0022] Furthermore, the annealing treatment is to transfer the cover glass after the salt dripping treatment to an annealing furnace at 410-430° C., lower the temperature to 100-110° C. within 140-200 minutes for annealing treatment, and then cool it to room temperature.
[0023] Furthermore, the above method also includes the step of cleaning:
[0024] Soak the annealed glass cover in water for 20-25 minutes, then take it out, rinse it with running water, and dry it naturally.
[0025] This embodiment also provides a cover glass prepared according to the above method for reducing the warpage of float chemically strengthened sodium aluminum silicate cover glass.
[0026] In summary, this application has the following beneficial effects:
[0027] 1. The method provided by the present application is to treat large-sized ultra-thin cover glass. Before chemical strengthening, the ultra-thin cover glass is inserted into the tempered frame in an inclined manner with the tin side facing downward. The inclination angle of the glass when inserted is 40-60°, preferably 50-55°. This chemical strengthening by placing it at an inclined angle at a specific angle can, on the one hand, use the component of the glass's own gravity perpendicular to the inclined surface downward to cause the glass to deform to offset the deformation caused by the stress difference between the air surface and the tin surface of the glass surface after strengthening, thereby reducing the warping value of the glass; on the other hand, by placing it at an inclined angle at this specific angle, the mass of molten salt taken away by the glass after strengthening is also significantly less than that of vertical placement and small angle placement (inclination angle less than 10°), which is beneficial to increase the number of recycling times of molten salt and can reduce the cost of chemical strengthening; at the same time, the tempered frame uses the current active strengthening jig of the cover factory, without the need for additional processing, which can further reduce costs.
[0028] 2. The method provided by the present application subjects the glass to be treated to three stages of preheating treatment before chemical strengthening, gradually increasing the temperature, and making the transition temperature difference between preheating, tempering and annealing small, thereby avoiding the warping of the tempered glass due to a large temperature difference encountered instantly, and also avoiding the edge collapse caused by thermal expansion and contraction.
[0029] 3. The method provided in the present application adopts a two-step mixed salt strengthening method. The first step is to slowly strengthen in a molten salt containing a low concentration of potassium nitrate (55-65%) to obtain a suitable stress layer compression depth; the second step is to quickly strengthen in a molten salt containing a high concentration of potassium nitrate (95-99%) to obtain a suitable glass surface compressive stress, which can reduce glass warping and avoid dimensional expansion of the glass during strengthening, thereby improving the qualified rate of the glass.
[0030] The embodiments of the present invention will be described in detail below in conjunction with examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially. DETAILED DESCRIPTION
[0032] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0033] Example 1
[0034] This embodiment provides a method for reducing the warpage of a float chemically strengthened sodium aluminum silicon cover glass, which comprises the following steps:
[0035] (1) Select a glass cover plate to be treated, with a thickness of 0.65 mm and an area of 420×260 mm, and polish the tin surface of the glass to reduce the thickness of the tin surface layer and reduce the tin content;
[0036] (2) Place the cover glass to be treated in a tempering rack in an inclined manner, with the tin surface of the cover glass facing downward. When the cover glass is inclined, the angle between the cover glass and the horizontal plane is 40°.
[0037] (3) Placing the tempered frame in a preheating furnace for gradient preheating treatment: placing the tempered frame in a preheating furnace at 190°C, completing the first stage of heating to 290°C within 50 minutes; then completing the second stage of heating to 370°C within 20 minutes; and completing the third stage of heating to 250°C within 50 minutes.
[0038] (4) The preheated cover glass is placed in a first molten salt (potassium nitrate: sodium nitrate = 60:40) at a temperature of 385° C. for strengthening for 9 hours; then, the cover glass is placed in a second molten salt (potassium nitrate: sodium nitrate = 97:3) at a temperature of 420° C. for strengthening for 2 hours.
[0039] (5) The strengthened glass was subjected to a salt dripping treatment at 380° C. for 15 min; the cover glass was then transferred to an annealing furnace at 420° C., the temperature was lowered to 105° C. within 170 min for annealing treatment, and then cooled at room temperature.
[0040] (6) Soak the annealed glass cover plate in water for 20-25 minutes, take it out, rinse it with running water, and dry it naturally to obtain tempered glass.
[0041] Embodiment 2-4
[0042] The difference between this group of embodiments and embodiment 1 is that the tilted placement angle of the glass is different:
[0043] Embodiment 2: When the cover glass is placed at an angle, the angle between the cover glass and the horizontal plane is 50°;
[0044] Embodiment 3: When the cover glass is placed tilted, the angle between it and the horizontal plane is 55°;
[0045] Embodiment 4: When placed at an angle, the angle between the cover glass and the horizontal plane is 60°.
[0046] For comparison, set the following comparison ratios at different angles:
[0047] Comparative Example 1: When placed, the angle between the cover glass and the horizontal plane is 0°, that is, placed horizontally;
[0048] Comparative Example 2: When placed, the angle between the cover glass and the horizontal plane is 20°;
[0049] Comparative Example 3: When placed, the angle between the cover glass and the horizontal plane is 70°;
[0050] Comparative Example 4: When placed, the angle between the cover glass and the horizontal plane is 90°, that is, placed vertically.
[0051] The obtained cover glass was evaluated for performance, and the results are shown in Table 1:
[0052] Table 1.
[0053]
[0054] It can be seen from Table 1 that for the cover glass with a specification of 420×260mm×0.65mm, the tilt angle at which the glass is placed during strengthening is closely related to the strengthening performance of the glass, the warping value, and the mass of salt taken away by the glass after strengthening. Specifically, when the glass tilt angle is 0-10°, although the glass warping value is low, the mass of molten salt taken away is as high as 13g; and when the glass tilt angle is 70-90°, although the mass of molten salt taken away is less, the warping value of the glass increases (above 0.70), which cannot meet the use requirements. In Examples 1-4 of the present application, the glass tilt angle is 40-60°, and the glass warping value is 0.33-0.40. Since the mass of molten salt taken away during chemical strengthening is also less, the number of times the tempered salt is used will not be significantly reduced. Compared with the prior art, in which the optimal warping value of the cover glass of 420×260mm×0.65mm can reach 0.75mm, the method provided in the present application can greatly reduce the warping value of the tempered glass (as low as 0.33) without damaging the number of times the molten salt can be recycled, and is technologically advanced.
[0055] It is obvious that after the glass is strengthened, the CS size of the glass surface is smaller than that of the air surface. At this time, the tin surface of the glass is downward, and the stress difference direction is perpendicular to the upward inclined surface, which causes the glass to deform and produce a "turtle warping" phenomenon. The glass is tilted and strengthened by using the component of the glass's own gravity perpendicular to the downward inclined surface to cause the glass to deform to offset the deformation caused by the stress difference between the air surface and the tin surface of the glass surface after strengthening, thereby reducing the warping value of the glass.
[0056] Embodiment 5-6
[0057] The difference between this group of embodiments and embodiment 1 is that the glass preheating method is different:
[0058] Example 5: The tempered frame is placed in a preheating furnace at 170°C, and the first stage of heating is completed within 60 minutes, heating to 270°C; then the second stage of heating is completed within 20 minutes, heating to 360°C; and the third stage of heating is completed within 40 minutes, heating to 410°C.
[0059] Example 6: The tempered frame is placed in a preheating furnace at 210°C, and the first stage of heating is completed within 40 minutes, heating to 310°C; then the second stage of heating is completed within 30 minutes, heating to 380°C; and the third stage of heating is completed within 50 minutes, heating to 440°C.
[0060] For comparison, the following comparisons of different preheating methods are set:
[0061] Comparative Example 5: The tempered frame was placed in a preheating furnace at 380° C. for 2 h.
[0062] Comparative Example 6: The tempered frame was placed in a preheating furnace at 190° C., and the temperature was raised to 280° C. within 60 min; and then the temperature was raised to 440° C. within 60 min.
[0063] The performance of the obtained cover glass was evaluated, and the results are shown in Table 2:
[0064] Table 2.
[0065]
[0066]
[0067] It can be seen from Table 2 that:
[0068] When chemical strengthening is performed after preheating using the gradient preheating program provided in Examples 1 and 5-6 of the present application, it helps to reduce the warpage of the glass and also avoid the occurrence of unqualified phenomena such as edge collapse. However, in Comparative Examples 5-6, since chemical strengthening is not performed after preheating in the gradient preheating program or after preheating in a larger gradient preheating program, the warpage value of the glass increases (above 0.70), which cannot meet the use requirements.
[0069] Examples 7-10
[0070] The difference between this group of embodiments and embodiment 1 is that the chemical strengthening steps of the glass are different:
[0071] Example 7: The preheated cover glass is placed in a first molten salt (potassium nitrate: sodium nitrate = 65:35) at a temperature of 385°C for strengthening for 9 hours; then the cover glass is placed in a second molten salt (potassium nitrate: sodium nitrate = 99:1) at a temperature of 420°C for strengthening for 2 hours.
[0072] Example 8: The preheated cover glass is placed in a first molten salt (potassium nitrate: sodium nitrate = 55:45) at a temperature of 385°C for strengthening for 9 hours; then the cover glass is placed in a second molten salt (potassium nitrate: sodium nitrate = 95:5) at a temperature of 420°C for strengthening for 2 hours.
[0073] Example 9: The preheated cover glass is placed in a first molten salt (potassium nitrate: sodium nitrate = 60:40) at a temperature of 390°C for strengthening for 8 hours; then the cover glass is placed in a second molten salt (potassium nitrate: sodium nitrate = 97:3) at a temperature of 430°C for strengthening for 2.5 hours.
[0074] Example 10: The preheated cover glass is placed in a first molten salt (potassium nitrate: sodium nitrate = 60:40) at a temperature of 380°C for strengthening for 10 hours; then the cover glass is placed in a second molten salt (potassium nitrate: sodium nitrate = 97:3) at a temperature of 410°C for strengthening for 1.5 hours.
[0075] For comparison, the following comparison ratios of different strengthening methods are set:
[0076] Comparative Example 7: The preheated cover glass was placed in a first molten salt (potassium nitrate: sodium nitrate = 35:65) at a temperature of 385° C. for strengthening for 9 hours; then the cover glass was placed in a second molten salt (potassium nitrate: sodium nitrate = 97:3) at a temperature of 420° C. for strengthening for 2 hours.
[0077] The performance of the obtained cover glass was evaluated, and the results are shown in Table 3:
[0078] Table 3.
[0079]
[0080] It can be seen from Table 3 that when the method in the embodiment of the present application is adopted, the preheated tempering frame is transferred to the tempering furnace and chemically strengthened twice in different concentrations of potassium nitrate molten salt. The first step is to slowly strengthen in a molten salt containing a low concentration of potassium nitrate (65%) to obtain a suitable stress layer compression depth, and the second step is to quickly strengthen in a molten salt containing a high concentration of potassium nitrate (97%) to obtain a suitable glass surface compressive stress, which can reduce glass warping and avoid dimensional expansion during glass strengthening. In the comparative example, when the first step is strengthened, the concentration of potassium nitrate in the molten salt is too low (35%), which will cause the stress layer compression depth of the glass to be too shallow. The second step is to quickly strengthen in a molten salt containing a high concentration of potassium nitrate (97%) so that the glass surface compressive stress and the stress layer compression depth of the glass increase rapidly, so that the glass expands in size during strengthening, resulting in an increase in the warping value of the glass (above 0.70), which cannot meet the use requirements.
[0081] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for reducing the warpage of a float chemically strengthened sodium aluminum silicon cover glass, characterized in that: The thickness of the cover glass is 0.4-0.7 mm, and the area of the cover glass is 420×260 mm; The method includes: The cover glass to be processed is placed in a tempering frame in an inclined manner, with the tin surface of the cover glass facing downward, and the angle between the cover glass and the horizontal plane is 40-60° when the cover glass is placed in an inclined manner; Placing the tempered frame in a preheating furnace and performing a gradient preheating treatment at 170-440° C.; The preheated tempered frame is transferred to a tempering furnace and chemically strengthened twice in potassium nitrate molten salt with different concentrations, and then salt dripping treatment and annealing treatment are performed in sequence.
2. The method for reducing warpage of float chemically strengthened sodium aluminum silicon cover glass according to claim 1, characterized in that: The gradient preheating treatment comprises: The tempered frame is placed in a preheating furnace at 170-210°C, and the first stage of heating is completed within 40-60 minutes, and the temperature is raised to 270-310°C; Then, the second stage of heating is completed within 10-30 minutes, and the temperature is raised to 360-380°C; The third stage of heating is completed within 40-60 minutes, and the temperature is raised to 410-440°C.
3. The method for reducing warpage of float chemically strengthened sodium aluminum silicon cover glass according to claim 2, characterized in that: The chemical strengthening includes: Putting the cover glass into the first molten salt for strengthening for 8-10 hours; The cover glass is then placed in a second molten salt and strengthened at a temperature of 410-430° C. for 1.5-2.5 hours.
4. The method for reducing warpage of float chemically strengthened sodium aluminum silicon cover glass according to claim 3, characterized in that: When strengthening is performed in the first molten salt, the temperature of the first molten salt is 380-390°C; when strengthening is performed in the second molten salt, the temperature of the second molten salt is 410-430°C.
5. The method for reducing warpage of float chemically strengthened sodium aluminum silicon cover glass according to claim 3, characterized in that: The first molten salt is a mixed solution of potassium nitrate and sodium nitrate with a concentration ratio of (55-65):(35-45).
6. The method for reducing warpage of float chemically strengthened sodium aluminum silicon cover glass according to claim 5, characterized in that: The second molten salt is a mixed solution of potassium nitrate and sodium nitrate with a concentration ratio of (95-99):(1-5).
7. The method for reducing warpage of float chemically strengthened sodium aluminum silicon cover glass according to claim 1, characterized in that: The temperature of the salt dripping treatment is 360-400° C. and the time is 5-20 min.
8. The method for reducing warpage of float chemically strengthened sodium aluminum silicon cover glass according to claim 7, characterized in that: The annealing treatment is to transfer the cover glass after the salt dripping treatment to an annealing furnace at 410-430° C., cool it down to 100-110° C. within 140-200 minutes for annealing treatment, and then cool it at room temperature.
9. The method for reducing warpage of float chemically strengthened sodium aluminum silicon cover glass according to claim 1, characterized in that: It also includes the steps of cleaning: Soak the annealed glass cover in water for 20-25 minutes, then take it out, rinse it with running water, and dry it naturally.
10. A cover glass prepared according to the method for reducing warpage of a float chemically strengthened sodium aluminum silicon cover glass according to any one of claims 1 to 9.
